Gambaran Tingkat Pengetahuan, Sikap Dan Perilaku Remaja Di Kecamatan Galang Tentang HIV/AIDS - Yosepha N, Dea Putri; Ompusunggu, Henny Erina Saurmauli; Martadinata, Maruatas Marojahan (Universitas HKBP Nommensen, 2023)
Background: Acquired immunodeficiency syndrome (AIDS) is a syndrome of disease due to decreased immune system caused Human Immunodeficiency Virus (HIV) and become a global problem, including Indonesia. Adolescents are group at risk for HIV/AIDS. Knowledge is important in determining attitude, attitude is a response to objects , attitude is a predisposing factor that can influence adolescent practice, so good knowledge about HIV/AIDS will help adolescent to make prevention. This study aims to identify of knowledge, attitudes and practice of adolescents about HIV/AIDS in Galang District, Deli Serdang Regency, North Sumatra.Objective: To identify the level of knowledge, attitudes and behavior of adolescents about HIV/AIDS in Galang District, Deli Serdang Regency, North Sumatra.Methods: This descriptive study used a cross-sectional approach conducted at Galang District High School in October 2022. The sample for this study was 104 senior students using cluster random sampling technique. Data was collected using a questionnaire that had been tested for validity and reliability with a Cronbach's Test Alpha value of 0.926; 0.871 and 0.827. Data were analyzed by univariate analysis.Results: The results of this study showed that the majority of respondents were 16 years old (70.2%), female (68.3%), grade 11 (70.2%), in social sciences (59.6%) and received information from the internet/social media (87.5%). The majority of respondents had a sufficient knowledge (57.7%), good attitude (79.8%) and good practice (99%).Conclusion: The majority of students at senior high school Galang District have sufficient knowledge about HIV/ AIDS, have a good attitude about HIV/ AIDS and are not at risk of contracting HIV/ AIDS.